Accumulate Content About LGBTQ+ Towards Attitude of Muslims on Instagram - Mahdalena, Vina; Utami, Riskha Fitriana; Nathanael, Garcia Krisnando (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
This study examines the attitude of Instagram followers @taulebih.id towards LGBTQ+ content on the Instagram provides information about sexual education based on an Islamic point of view. One of them is the Instagram account @taulebih.id which often provides information about LGBTQ+ to give a complete picture of the LGBTQ+ community from an Islamic viewpoint. This study uses a quantitative method with an explanatory approach. The information integration theory states accumulate information has latent power and can influence individuals to have certain attitudes. Information Integration Theory focuses on how individuals collect and organize information about accumulate information to act positively or negatively towards attitude objects. Researchers used questionnaire on Instagram with 100 respondents. The results of hypothesis testing using the t-test show that the influence of LGBTQ+ content @taulebih.id with the valance and weight dimensions significantly affects followers' attitudes. The results obtained by Ha are accepted, which means that there is a significant influence on the attitude of followers or followers who agree with the statements in the @taulebih.id account. This can be proven from the data results of t count 14.789 which is greater than t table, namely 1.292 so that it can be concluded that the hypothesis is accepted. Â